THE RELATIONSHIP BETWEEN DORMITORY LIFESTYLE AND CHRISTIAN CHARACTER AMONG COLLEGE STUDENTS: A Correlation Study at the Faculty of Education, Pelita Harapan University - Abednego Tri Gumono; Year Rezeki Patricia Tantu (QUAERENS: Journal of Theology and Christianity Studies, 2026)
In fostering Christian character, the Faculty of Education at Pelita Harapan University has established a dormitory system for students. Through this residential living arrangement, the Faculty of Education aims to produce graduates with a holistic profile, encompassing teaching competence, faith, and character. According to the results of a tracer study on student character in 2015, 60% of students fell into the “good” category, while in 2020, this figure rose to 61%. These data indicate that character development, particularly Christian character, remains an area that requires continuous improvement. This study aims to investigate the relationship between the dormitory lifestyle and the formation of Christian character among students. Christian character is measured across the dimensions of love, kindness, goodness, and gentleness. The boarding school lifestyle was measured in terms of spirituality, discipline, and social life. The research method used was a quantitative correlation method. The strength of the relationship was measured using the Morgan scale. The results showed a correlation coefficient for the dormitory lifestyle of 0.473 (moderate relationship) with a coefficient of determination/r² value of 0.2237 (22%). Thus, the dormitory lifestyle variable (independent variable) accounts for 22% of the variation in the formation of students’ Christian character (dependent variable). This moderate correlation between dormitory living patterns and Christian character indicates that the formation of Christian character is also influenced by other factors such as faculty members, the implementation of the Christian curriculum, and peers. Interviews conducted with 15 students revealed that 13 (86%) stated that faculty members have served as role models in character by behaving fairly, firmly, and appropriately time, and consistency. The integration of the Christian curriculum has been consistently implemented across curriculum subjects. Peers influence positive motivation in students’ completion of academic assignments and committee work. The next data point shows that 2 (14%) students stated that faculty members are already quite good at serving as role models of character and integrating the Christian curriculum, although this does not yet apply to all faculty members. The recommendation from this study is that Christian character development should be carried out in an integrated manner involving faculty professionalism, the implementation of a Christian curriculum, the student affairs department, the counseling department, and the dormitory management department/ Mission Youth for Christ.